Radiation-Induced Neoplastic Transformation , Hormesis and Risk Assessment - J. Leslie Redpath PhD; Eugene Elmore PhD (SAGE Publishing, 2007)
Dose-response curves for various low-LET radiation sources have consistently been demonstrated to be J-shaped for the cancer-relevant endpoint of neoplastic transformation in vitro. Most of these studies have been performed where the radiation has been delivered at intermediate to high dose-rates (30-3000 mGy/min), where the threshold dose for induction of neoplastic transformation is around 100-200 mGy. Below these doses, the transformation frequency is less than that seen spontaneously, indicative of a hormetic effect. More recently, data have been obtained for low dose rates (<0.5 mGy/min) of low-LET radiation, and again hormetic effects are apparent but with threshold doses now being >1000 mGy. Similar trends have been reported in animal experiments as well as in human epidemiologic studies. Indeed, the relative risks for induction of neoplastic transformation in vitro in the dose range 1 to 1000 mGy agree well with those for incidence of radiation-induced breast cancer and leukemia in humans. These findings support the notion that the endpoint of neoplastic transformation in vitro is a plausible endpoint to not only study mechanisms involved in response to low doses of radiation, but also to provide information of potential importance to risk assessment.